The Role of Customs Regulations and Policies in Encouraging MSME Exports: A Case Study on MSMEs in the Creative Industry Sector - Rivaldo Kurniawan; Sudarmiatin; Heri Pratikto (Abadi Institute, 2026)
This study aims to analyze the role of customs regulations and policies in encouraging the export activities of Micro, Small, and Medium Enterprises (MSMEs), especially in the creative industry sector. This study uses a qualitative approach with a case study method on one of the creative industry MSMEs that has expanded to the international market. Data collection techniques are carried out through in-depth interviews, observations, and documentation, while data analysis uses an interactive model that includes data reduction, data presentation, and conclusions drawn. The results of the study show that government regulations and customs policies have a strategic role in increasing MSMEs' access to global markets, especially through simplifying export procedures, providing customs facilities, and digitizing export services. However, there are still a number of obstacles faced by MSMEs, such as low understanding of regulations, administrative complexity, and limited human resources in managing export documents. Therefore, synergy is needed between the government, business actors, and other stakeholders to increase regulatory literacy, strengthen export assistance, and optimize the implementation of policies that are more inclusive and adaptive to the needs of MSMEs. This research provides practical implications for the development of MSME internationalization strategies as well as theoretical contributions in the study of MSME-based public policy and international trade.